Response of Boro Rice to Planting Stage of Seedlings and Nutrient Management under SRI - Sen, Dhiman; Maity, Swapan Kumar; Mukhopadhyay, Prabir (International Journal of Bio-resource and Stress Management, 2023)
The current research work was carried out at the experimental field of Dakshin Dinajpur Krishi Vigyan Kendra, Majhian, South Dinajpur, West Bengal during Boro 2011-12 season. The experiment was laid out in factorial RBD design and replicated thrice. There were total twenty treatments out of which eighteen treatments were comprised of factorial combinations of two planting stages (planting at two leaved stage and three to four leaved stage), three sources of organic nutrients (FYM 10 t ha-1, FYM 5 t ha-1 and FYM 5 t ha-1 +Azospirillum biofertilizer) and three modes of N application (blanket split as ¼ basal+½ active tillering+¼ panicle initiation, LCC based N application at critical value 3 and at critical value 4). The experiment included two absolute controls under each planting stage i.e. transplanting at two leaved stage and transplanting at three to four leaved stage. Two leaved stage transplanted treatment significantly increased plant height, number of tiller hill-1, dry matter production m-2, effective tillers hill-1, filled grains panicle-1, test weight, grain and straw yields in comparison to transplanting at three to four leaved stage. Among organic sources of nutrient, FYM 10 t ha-1 recorded significantly taller plant, more number of tiller hill-1, higher dry weight per square meter, effective tillers hill-1, filled grains panicle-1, test weight, grain and straw yields followed by FYM 5 t ha-1+Azospirillum. On an average LCC treatments provided better response to obtain higher grain as well as straw yields and in between LCC based N applications, LCC at 4 showed better result than LCC at 3.